2261. Phosphaturia in HIV-Exposed Uninfected Neonates Associated With Maternal Use of Tenofovir Disoproxil Fumarate in Late Pregnancy. (26th November 2018) - Purswani, Murli; Jacobson, Denise; Kopp, Jeffrey; Van Dyke, Russell; DiMeglio, Linda; Yao, Tzy-Jyun; Miller, Tracie; Siberry, George; ,
Abstract: Background: Our recent study showed significantly lower bone mineral content (BMC) in HIV-exposed uninfected (HEU) neonates born to HIV-infected (HIV+) mothers who took tenofovir disoproxil fumarate (TDF) in late pregnancy compared with no TDF use. In this cohort we sought to understand possible mechanisms for lower BMC by comparing markers of bone metabolism and renal function with TDF exposure in HEU neonates. Methods: Among a subset of HEU children in the multicenter (United States and Puerto Rico) observational Surveillance Monitoring for ART Toxicities (SMARTT) Cohort study, we enrolled neonates (≥36 weeks gestational age) of HIV+ mothers who took TDF for ≥8 weeks in the third trimester (TDF+) or no TDF in pregnancy (TDF-). In addition to BMC measures, we collected a blood and urine sample on each child ≤30 days of birth to measure serum creatinine, phosphate, 25-OH vitamin D, parathyroid hormone and urine creatinine, phosphate and N-terminal telopeptide. Standard equations were used to estimate proximal tubular phosphate reabsorption and glomerular filtration rate (eGFR). Comparisons were made by TDF exposure using Wilcoxon and Fisher's exact tests. We fit linear models to compare TDF+ and TDF− for each assay by age in days at sample collection (slope), stratified by age group at sample collection time (0–3 days, 4–30 days). Results: Of 160 HEU neonates (Black 71%, Hispanic 31%), 82 were TDF+ and 78 TDF−. Sociodemographic and anthropometric characteristics did not differ by TDF exposure in each age group. Within 0–3 days of life, TDF+ had a greater decline in serum creatinine ( P = 0.04) and a greater increase in eGFR compared with TDF− ( P = 0.06), but no difference in slope by TDF exposure within 4–30 days of life, nor in serum phosphate in either age group. Proximal tubular phosphate reabsorption was similar for both groups within the first 3 days of life, with a significantly greater decline in phosphate reabsorption between 4 and 30 days of life in the TDF+ compared with the TDF− group ( P = 0.006, Figure 1). Bone markers did not differ by TDF exposure for either age group. Conclusion: Urinary phosphate loss was increased among HEU neonates of mothers who took TDF in late pregnancy. This suggests proximal tubular dysfunction and may explain, at least in part, the decrease in BMC previously described. Disclosures: R. Van Dyke, Giliad Sciences: Grant Investigator, Research grant.